DRAMATURGY: SCRIPT AND THEATER STAGE PERFORMED BY AMATEUR “ACTORS DIRECTED” AB ASMARANDANAPRAWIRA - Asep Wasta; Arni Apriani (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Performing art is the realization of working ideas as outlined by the creator in an art presentation that contains artistic aesthetics that can be enjoyed by the audiences.. Theatrical art is essentially from several art dimensions, including: dance (movement), fine arts, literary arts and music. This article examines the work of the theatrical play "Aktor Amaitr" by director AB. Asmarandana played by the Ngaos Art Theater Group in Tasikmalaya, West Java. To understand the creative process, it is examined through the dramaturgy of the show, both the dramaturgy of the script and the stage dramaturgy which can be seen from the process of working on the script along with its literary management as well as the arrangement of the artistic elements of the stage. and other supporting aesthetic elements as part of the performance form, It uses a qualitative research method with a phenomenological approach that is described in an analytical descriptive manner. Referring to Irving Goffman's dramaturgical theory, this Amateur Actor's theatrical performance implies a message that interprets the daily life of humans in this case is an actor who plays a show on stage both from the front stage and back stage.